Pengaruh Substitusi Tepung Kacang Hijau Terhadap WarnaDan Daya Terima Beras Analog Dari Tepung Talas - Palupi, Endah (2016)
ENDAH PALUPI. J310110108 SUBSTITUTION EFFECT ON COLOR GREEN BEAN FLOUR AND POWER RECEIVED FROM ANALOG RICE FLOUR TARO Background. Rice is the staple food rice Indonesia.Konsumsi society in Indonesia in 2014 amounted to 96.32 kg / capita / year . This is due to the diversity of food consumption has not materialized . Talas flour contains high nutrient and can be processed into rice analog . Green pea flour can be used as a substituent taro flour to increase the protein content of rice . Objective. The purpose of this study was to determine the effect of substitution of the color green bean flour and rice received power analog of taro flour . Research method. The study design used was completely randomized design with 3 treatments mung bean flour substitution of 5% , 10 % and 15 % . Data analisiswarna , and acceptance nce analogdianalisis using one way ANOVA statistical test and then if there are differences continued test of Duncan with 95% significance level . Result. The results showed that there is no substitution effect on the value of mung bean flour a nce analog . Nce a value analog ranges from 1.4 to 1.54 . There is a green bean flour substitution effect on the value of L and b nce analog . The highest L value is 54.33 . The highest value is 7.64 b . There is a substitution effect of mung bean flour to the acceptance of color , aroma , flavor , and overall nce analog . Score the highest color acceptability is 3.48 , for the aroma is 3.2 , for the flavor was 3.28 , and for the entire 3.37 . There is no substitution effect mung bean flour to the received power analog rice rice texture . Scores acceptability texture ranges from 2.65 to 3.11 . Conclusion. based on the acceptance of panelists, suggested substitusi5 % mung bean flour rice flour-based analog talas .